177 Ejaculation Profiles in Men after Irreversible Electroporation for Prostate Cancer. (1st May 2022) - Martinez, J. Flores; Benfante, N.; Chen, L.; Ehdaie, B.; Mulhall, J.P.
ABSTRACT: Introduction: Irreversible Electroporation (IRE) is an evolving strategy for the management of localized prostate cancer. Little data exists on sexual function, in particular ejaculation, in such patients. Objective: We aimed to report the ejaculatory function in patients undergoing IRE. Methods: Patients undergoing IRE with ≥1-year follow-up were evaluated. These patients were selected for focal therapy and consented to participate in a prospective registry. Eligibility criteria: Gleason score 3+4, PSA <20, no evidence of extracapsular extension, seminal vesicle invasion or lymph node involvement on standard imaging. The Gleason score 3+4 prostate cancer was allowed up to a maximum of two adjacent sextants within the prostate gland. Concomitant Gleason score 6 was untreated and monitored on active surveillance. They completed the Male Sexual Health Questionnaire ejaculation domain short form (MSHQ-EFD-SF) at 6 weeks, 3 months, 6 months, and 12 months post-IRE. This questionnaire has 4 questions: 3 questions sum scores (range 1-15), where lower scores indicate worse ejaculatory function, and the MSHQ-Bother question score (ranges 0-5), with higher scores indicating higher bother associated with ejaculatory difficulties. Comorbidities, demographics, and pathology parameters were recorded. Results: 20 men have been evaluated to date with a mean age of 64.3 ± 4.8 years. Baseline testosterone and PSA were 536.3 ± 267.6 ng/dL and 6.2 ± 2.7 ng/mL. Mean prostate volume was 45.6 ± 11.9 cc. Median baseline score of MSHQ-EJD-SF was 13.5 (IQR 10, 14), and post-procedure median scores were 11 at 6 weeks; 12.5 at 3 months; 12 at 6 months; and 11.5 at 12 months (p-value =0.036). Scores for ejaculation strength and seminal volume ejaculated decreased significantly, and bother scores increased significantly between baseline and 1-year post-IRE. The ability to ejaculate during sexual activity did not change over time. Conclusions: In our cohort of patients with prostate cancer who underwent IRE there was a significant difference in ejaculatory profiles between baseline and 1-year post-IRE. Disclosure: Work supported by industry: no.